Rational Strategies for the Selective Functionalization of Calixarenes. Issue 8 (2nd July 2015) - Lavendomme, Roy; Zahim, Sara; De Leener, Gaël; Inthasot, Alex; Mattiuzzi, Alice; Luhmer, Michel; Reinaud, Olivia; Jabin, Ivan
Abstract Calixarenes are widely used as molecular platforms in supramolecular chemistry. Their efficient modification is key for appending functional moieties such as binding, sensing, chiral, or hydrophilic subunits. Due to the presence of multiple identical functional groups, selective functionalization of such macrocyclic compounds is highly challenging. Indeed, the control of the chemo‐, regio‐, stereo‐ as well as iteroselectivity is required. This review describes rational methods leading to a high degree of regio‐ and/or iteroselectivity and classifies them into specific strategies. Many of these strategies are conceptually very general and hopefully will be a source of inspiration for developing selective methods for other macrocyclic platforms.